Ecuador : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2015)
This Selected Issues paper presents an assessment of macro-financial stability in Ecuador. Ecuador is being hit by external shocks that imply a downward adjustment in growth and financial intermediation. The financial system has been liquid and well-capitalized through 2014, but recently pressures on liquidity positions as well as credit and interest risks have been on the rise. Although main financial stability indicators do not show signs of stress in the first half of 2015, the developments warrant close monitoring and rapid reactions if pressures continue.